(untitled) (Huellas, 2026)
Housing construction has historically been viewed as a male-dominated field. However, in Amaicha del Valle, earthen architecture is developed within a community fabric featuring active female participation. This study analyses the role of women in the production of the built environment from a gender and everyday life perspective, positioning the domestic space and its daily dynamics as the analytical core, as it constitutes a fundamental element in the construction and overall sustainability of the rural built environment. Based on fieldwork (2017–2023) involving interviews and participant observation focused on earthen construction, the study highlights that women play central roles: they design spaces, transmit knowledge, manage resources, make technical decisions and prepare materials. These practices are intertwined with the productive and reproductive activities for which they are responsible, which poses an even greater challenge. However, this leading role remains invisible under prevailing patriarchal logics. By addressing these tensions, the study contributes to discussions on the production of habitat through a situated perspective, intertwining the gender perspective with the ways of living characteristic of the rural context.